A case report of pulmonary paragonimiasis diagnosed via the deterioration of pulmonary cavities during high-dose corticosteroid therapy for chronic eosinophilic pneumonia - Takehiro Hashimoto; Akira Nishizono; Kazufumi Hiramatsu (Annals of Thoracic Medicine)
A 32-year-old Chinese woman with a cough and bloody sputum was diagnosed with chronic eosinophilic pneumonia. After starting corticosteroid therapy, chest radiography showed improvement in the bilateral infiltrative shadow. However, chest image findings showed worsening of the bilateral infiltrative shadow and pulmonary cavities during the 20 mg/day of oral prednisolone therapy. Transbronchial lung biopsy and bronchoalveolar lavage were repeated, and the patient was diagnosed with pulmonary paragonimiasis. After starting praziquantel treatment, chest radiography findings and clinical symptoms improved. Careful follow-up during corticosteroid therapy is important to judge whether transient improvement and true deterioration of radiological findings.